2021
DOI: 10.3390/ijerph18157722
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Index and Clinical Outcomes of Severe COVID-19: Preliminary Results of a Cross-Sectional Study

Abstract: The potentially detrimental effects of the worldwide deficiency of Omega-3 fatty acids on the COVID-19 pandemic have been underestimated. The Omega-3 Index (O3I), clinical variables, biometric indices, and nutritional information were directly determined for 74 patients with severe COVID-19 and 10 healthy quality-control subjects. The relationships between the OI3 and mechanical ventilation (MV) and death were analyzed. Results: Patients with COVID-19 exhibited low O3I (mean: 4.15%; range: 3.06–6.14%)—consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 35 publications
0
31
0
1
Order By: Relevance
“…In terms of PUFAs and severity of Covid-19 disease, the mean omega-3 PUFA Index (consistent with insufficient fish and Omega-3 supplement consumption) was 4.15% ± 0.69% in patients with severe Covid-19 and markedly lower than the healthy control subjects (mean: 7.84%; range: 4.65–10.71%) [32] .…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…In terms of PUFAs and severity of Covid-19 disease, the mean omega-3 PUFA Index (consistent with insufficient fish and Omega-3 supplement consumption) was 4.15% ± 0.69% in patients with severe Covid-19 and markedly lower than the healthy control subjects (mean: 7.84%; range: 4.65–10.71%) [32] .…”
Section: Resultsmentioning
confidence: 72%
“…In terms of requirement to mechanical ventilation, Zapata et al showed that the need for mechanical ventilation for low omega-3 PUFA values (lowest O3I quartile (<3.57%)) increased compared to higher values (OR = 1.348, 95% CI: 0.925–1.964; P = 0.183) and decreased for high levels of omega-3 PUFA (highest O3I quartile (> 4.51%) (OR = 3.111, 95% CI: 1.261–7.676; P = 0.032) [32] .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…found that plasma GLA, DGLA, and EPA were decreased in COVID-19 patients, but LA and AA were elevated (12). Two small studies found that the omega-3 index was significantly lower in COVID-19 patients and was inversely associated with risks of requiring mechanical ventilation and death (9, 10). The differences in these observational studies are likely results of uncontrolled confounding factors or the usage of patients at different disease stages.…”
Section: Discussionmentioning
confidence: 99%
“…Recent observational studies have noted significant changes in the circulating levels of various PUFAs when comparing COVID-19 patients to healthy controls and across severity subgroups of patients. In general, total PUFAs, omega-6 PUFAs, linoleic acid (LA), and the omega-3 index measured as the percentage of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in red blood cell (RBC) fatty acids, are lower in COVID-19 patients and even lower in severe cases (9)(10)(11)(12). A higher omega-3 index in patients was further associated with lower risks of requiring mechanical ventilation and death (9,10).…”
Section: Introductionmentioning
confidence: 99%